Sensory Transduction in Photoreceptors and Olfactory Sensory Neurons: Common Features and Distinct Characteristics - Genovese, Federica; Reisert, Johannes; Kefalov, Vladimir J. (Frontiers in Cellular Neuroscience, 2021)
The past decades have seen tremendous progress in our understanding of the function of photoreceptors and olfactory sensory neurons, uncovering the mechanisms that determine their properties and, ultimately, our ability to see and smell. This progress has been driven to a large degree by the powerful combination of physiological experimental tools and genetic manipulations, which has enabled us to identify the main molecular players in the transduction cascades of these sensory neurons, how their properties affect the detection and discrimination of stimuli, and how diseases affect our senses of vision and smell. This review summarizes some of the common and unique features of photoreceptors and olfactory sensory neurons that make these cells so exciting to study.